Application of Piezofilms for Excitation and Active Damping of Blade Flexural Vibration - PESEK, Ludek; PUST, Ladislav; BULA, Vitezslav; CIBULKA, Jan (Archives of Acoustics, 2015)
The steam turbine blades of low pressure stages are endangerd by the high-cyclic fatigue due to the combined loading of dynamic stresses by the steam time-variant pressure and the pre-stress from centrifugal forces. Therefore, the importance of their experimental dynamic analysis in the design stage is critical. For laboratory tests of the blades, the piezo actuators placed on the blades, unlike electromagnets placed in the stationary space, give a possibility to excite the flexural vibration of the blades within the bladed disk by time continuous forces independently of the rotor revolutions. In addition, the piezo actuators can be also used to control the vibrations of the blade. Therefore, several dynamic experiments of the clamped model blade equipped with PVDF films were performed for the force description of the piezo foils and their behavior as actuators of the blade vibration. The numerical beam models were used for numerical analysis of the vibration suppression effects both by additional parametric excitation and by active damping. The optimal phase shift of piezo actuator voltage supply was ascertained both for amplitude amplification and suppression. The results contribute to the knowledge of the actuation and active damping of blade vibration by the piezo elements.